Effectiveness of Open-Ended Psychotherapy Under Clinically Representative Conditions - Nordmo, Magnus; Sønderland, Nils Martin; Havik, Odd E.; Eilertsen, Dag-Erik; Monsen, Jon T.; Solbakken, Ole Andre (Frontiers in Psychiatry, 2020)
Objective This study investigates the effectiveness of open-ended psychotherapy in a large, naturalistic, and diverse patient cohort using rigorous and multifaceted assessments. Method Patients (N = 370) in open-ended psychotherapy completed an extensive set of self-report measures and diagnostic interviews, including long-term follow-up in order to assess stability of outcomes. About half of the patients qualified for a personality disorder at the onset of treatment. Treatments were open-ended, and on average therapists provided substantially larger treatment doses than common in the literature. Results A substantial majority recovered from their respective Axis I (58%) and/or Axis II (55%) disorders during treatment. Patients also experienced large positive changes in self-report measures of overall psychiatric symptoms and moderate positive changes in self-reported interpersonal problems, while very few (< 3%) demonstrated negative development. The patients maintained their diagnostic and self-assessed changes at a two-and-a-half-year follow-up. In contrast, self-reported occupational functioning showed minimal improvement throughout the treatment and follow-up phase. Conclusion A naturalistic patient cohort undergoing open-ended psychotherapy demonstrates substantial and stable improvements.